Evaluation of the Review Models and Approval Timelines of Countries Participating in the Southern African Development Community: Alignment and Strategies for Moving Forward - Sithole, Tariro; Mahlangu, Gugu; Capote, Velma; Sitoie, Tania; Shifotoka, Saren; Gaeseb, Johannes; Danks, Lorraine; Nkambule, Portia; Juma, Alex; Fimbo, Adam; Munkombwe, Zuma; Mwale, Bernice; et al. (Frontiers in Medicine, 2021)
Introduction: Regulatory reliance, harmonisation and work sharing have grown over the last few years, resulting in greater sharing of work and information among regulators, enabling efficient use of limited resources and preventing duplication of work. Various initiatives on the African continent include ZaZiBoNa, the Southern African Development Community (SADC) collaborative medicines registration initiative. ZaZiBoNa has resulted in great savings in time and resources; however, identified challenges include lack of clear information regarding the participating countries registration processes and requirements as well as lengthy registration times. The aim of this study, therefore, was to compare the data requirements and review models employed in the assessment of applications for registration, the target timelines for key milestones and the metrics of applications received and approved in 2019 and 2020 by Mozambique, Namibia, South Africa, Tanzania, Zambia and Zimbabwe. Methods: A senior member of the division responsible for issuing marketing authorisations completed an established validated questionnaire, which standardises the review process, allowing key milestones, activities and practices of the six regulatory authorities to be identified and compared. The completed questionnaires were validated by the heads of the respective agencies. Results: The majority of applications received and approved by all six agencies in 2019 and 2020 were for generics. The mean approval times for generics varied across the countries, with ranges of 218–890 calendar days in 2019 and 158–696 calendar days in 2020. All three types of scientific assessment review models were used by the six agencies and data requirements and extent of scientific assessment were similar for five countries, while one conducted full reviews for new active substances. A large variation was observed in the targets set by the six agencies for the different milestones as well as overall approval times. Conclusions: The study identified the strengths of the countries as well as opportunities for improvement and alignment. Implementation of the recommendations made as in this study will enhance the countries’ individual systems, enabling them to efficiently support the ZaZiBoNa initiative.